Effect of integrated nitrogen management on soil properties and enzymatic activities - YADAV, POONAM KUMARI; YADAV, B L; YADAV, BASU DEVI; YADAV, SHITAL; YADAV, SURESH (The Indian Journal of Agricultural Sciences, 2020)
A field experiment was conducted at Agronomy farm, of S K N College of Agriculture, Jobner (Rajasthan) during kharif season 2017 in loamy sand soil with an objective “Effect of Integrated nitrogen management on soil properties in pearlmillet [Pennisetum glaucum (L.) R. Br. Emend Stuntz]”. The experiment was laid out in factorial randomized block design with three replications, comprised eight treatments of sources of nitrogen (Control, 50% RDN through urea+ 50% RDN through vermicompost, 50% RDN through urea+ 50% RDN through FYM, 75% RDN through urea+ 25% RDN through vermicompost, 75% RDN through urea+ 25% RDN through FYM, 100% RDN through urea, 100% RDN through vermicompost and 100% RDN through FYM) and two treatments of biofertilizer (without inoculation and with Azotobacter) were applied to the pearlmillet var. RHB-173. The application of sources of nitrogen,soil organic carbon, available nitrogen, phosphorus, potassium, dehydrogenase activity and alkaline phosphataseactivity were increased significantly with the application of 75% RDN through urea+ 25% RDN through vermicompost at flowering and harvest stage.The soil organic carbon, available N, P2O5, K2O, dehydrogenase activity and alkaline phosphates activities were also increased when inoculated with biofertilizer.